2013
DOI: 10.4187/respcare.01828
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Function of Patients with Chronic Neck Pain: A Spirometry Study

Abstract: BACKGROUND: Chronic neck pain is one of the most common musculoskeletal pain conditions experienced by many people during their lives. Although patients with neck pain are managed predominantly as musculoskeletal patients, there are indications that they also have poor pulmonary function. The aim of this study was to examine whether patients with chronic neck pain have spirometric abnormalities and whether neck pain problems and psychological states are associated with these abnormalities. METHODS: Forty-five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
3
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 34 publications
0
43
3
4
Order By: Relevance
“…The authors suggested that patients with CNP do not have optimal pulmonary function. In contrast with the aforementioned studies, we found no significant difference regarding all PFTs between the patients and controls either both gender (Table ). Because neck muscles are not used actively in normal breathing, we think that pulmonary functions are unaffected by neck pain in patients with CNP.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The authors suggested that patients with CNP do not have optimal pulmonary function. In contrast with the aforementioned studies, we found no significant difference regarding all PFTs between the patients and controls either both gender (Table ). Because neck muscles are not used actively in normal breathing, we think that pulmonary functions are unaffected by neck pain in patients with CNP.…”
Section: Discussioncontrasting
confidence: 99%
“…found a weakness in the respiratory muscles of patients with CNP. In another study, they compared the PFTs between individuals with neck pain and healthy controls . They found that the values for vital capacity, FVC, expiratory reserve volume and MVV were lower than in controls, but PEF, FEV 1 and FEV 1 /FVC ratio were not different between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…While the study analyzed the changes in respiratory functions in individuals with chronic neck pain, it showed that VC, ERV, FVC, and maximal voluntary ventilation parameters were lower in individuals with neck pain, and considering the relationship between TKS and the decrease in the parameters, they found that it was negatively related to VC and maximal voluntary ventilation, and not related to the PEF value. [33] No study was found to be investigating the relationship between kinesiophobia and respiratory functions in individuals with AS.…”
Section: Discussionmentioning
confidence: 99%
“…Vital capacity and functional vital capacity are significantly lower, and maximal voluntary ventilation is also lower, in CNP patients than in people without CNP [3,4]. It was revealed that respiratory muscle strength has a significant correlation with CNP [4][5][6].…”
Section: Introductionmentioning
confidence: 94%
“…In addition to musculoskeletal pain, neck pain is also associated with dizziness, anxiety, and depression, and is known to cause disability in daily life [2]. Recently, some evidences showing that pulmonary function is reduced in patients with chronic neck pain (CNP) have been reported [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%